The relationship between meaning in life and self-regulated learning among college students: the mediating effect of psychological capital and the moderating effect of phubbing - Wenjing Feng; Peibo Wu; Shuai Lv; Zhaoyuan Fan (BMC Psychology)
Abstract Background Previous research on college students’ learning problems has investigated the notion of self-regulated learning. However, relatively little research has explored the mechanism underlying the relationship between meaning in life and self-regulated learning on the basis of the self-regulated learning framework. Additionally, relatively few studies have examined the impact of phubbing behavior on the traits exhibited by the source of the behavior in question, particularly from the perspective of nonpersonal perception. Therefore, in this study, Pintrich’s Self-Regulated Learning model is used as a theoretical framework; in addition, this study draws on conservation of resources theory, among other theories, to explain the relationships among relevant variables. It thus aims to develop a moderated mediation model that can be used to systematically examine the relationship between meaning in life and self-regulated learning as well as the mechanism underlying this relationship. On this basis, this study provides effective recommendations that can be used to enhance self-regulated learning among college students and promote high-quality learning outcomes. Methods In this study, the Chinese Meaning in Life Questionnaire, the Youth Psychological Capital Questionnaire, the Youth Phubbing Scale-Chinese Version, and the Self-Regulated Learning Scale for College Students were used to survey 488 college students who were recruited from an undergraduate college in a province in central China. Results (1) Meaning in life had a positive predictive effect on self-regulated learning (r 2 = 0.51, p < 0.001). (2) Psychological capital mediated the relationship between meaning in life and self-regulated learning (indirect effects = 0.31, SE = 0.04, 95% CI=[0.23–0.38]). (3) The first half of the mediating path “meaning in life → psychological capital → self-regulated learning” and the direct path “meaning in life → self-regulated learning” were moderated by phubbing (β = 0.07, p < 0.01, β = 0.10, p < 0.001). Conclusion Meaning in life not only predicts self-regulated learning among college students directly and positively; it also influences self-regulated learning indirectly via the mediation of psychological capital. The effects of meaning in life on psychological capital and self-regulated learning are moderated by phubbing. Specifically, as the frequency of phubbing increases, the positive predictive effects of meaning in life on psychological capital and self-regulated learning become stronger.